1973
DOI: 10.1104/pp.52.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an Aminotransferase of Pea (Pisum sativum L.)

Abstract: A transaminase (aminotransferase, EC 2.6.1) fraction was partially purfied from shoot tips of pea (Pisum sativum L. cv. Transaminases (aminotransferases, EC 2.6. 1), particularly those of plants, are quite incompletely described in regard to their amino acid and keto acid specificities. Some partially purified preparations are highly specific for particular amino acids (1, 2, 5, 30). Other preparations reportedly transaminate a variety of amino acids (7,8,12,15,25,29). Many workers have concentrated on transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…However, the enzyme activity was lost upon attempted further purification. The characteristics found for this enzyme match the findings for tryptophan aminotransferase in other plants (10,12,19 this enzyme is clearly present in all species examined and it can be concluded that in these species of Nicotiana, tryptophan aminotransferase, indoleacetaldehyde oxidase, and indoleacetaldehyde reductase are gene products ofpotentially crucial importance in the metabolic pathway leading from tryptophan to IAA. Conversely, it appears from the results obtained here that tryptophan decarboxylase and tryptamine are not significantly involved in this pathway.…”
supporting
confidence: 66%
“…However, the enzyme activity was lost upon attempted further purification. The characteristics found for this enzyme match the findings for tryptophan aminotransferase in other plants (10,12,19 this enzyme is clearly present in all species examined and it can be concluded that in these species of Nicotiana, tryptophan aminotransferase, indoleacetaldehyde oxidase, and indoleacetaldehyde reductase are gene products ofpotentially crucial importance in the metabolic pathway leading from tryptophan to IAA. Conversely, it appears from the results obtained here that tryptophan decarboxylase and tryptamine are not significantly involved in this pathway.…”
supporting
confidence: 66%
“…The in vitro enzyme assay using recombinant TAA1 was performed according to the previously described borate buffer assay (Matheron and Moore, ; Tao et al ., ) with minor modifications. The reaction mixture was prepared in 500 μl of 500 m m borate buffer (pH 8.5) containing 300 μ m l ‐Trp, 1 m m sodium pyruvate, 10 μ m pyridoxal phosphate (PLP), 1 μg of purified TAA1 recombinant protein and the test compound at 30 μ m .…”
Section: Methodsmentioning
confidence: 99%
“…The tryptophan aminotransferase activity was determined by the previously described method (Matheron and Moore 1973; Khandaswami and Vaidyanathan 1973) with some modifications. The final assay concentration contained 0·5 ml of enzyme extract and 2·5 ml of 0·5 mol borate buffer (pH 8·5) containing 0·1 μmol of pyridoxal phosphate, 40 μmol of l ‐tryptophan and 20 μmol of α‐ketoglutarate.…”
Section: Methodsmentioning
confidence: 99%